Mencegah kekambuhan pada pecandu narkoba: Bagaimana peranan craving dan dukungan keluarga? Preventing relapse in drug addicts: What is the role of craving and family support? - Pratitis, Niken Titi; Fananni, Muhammad Rizky (Persona:Jurnal Psikologi Indonesia, 2024)
Previous research data shows that drug users who have undergone rehabilitation can still experience relapse, so research that identifies factors that cause relapse is essential. This study aims to examine the relationship between craving and family support with the tendency to relapse. The research participants were 97 drug addicts undergoing rehabilitation at several rehabilitation institutions in Surabaya and Gresik. The research scale was compiled by the researcher himself, consisting of a relapse scale (α = 0.935), which refers to the theory of Gorski and Miller, a craving scale (α = 0.899), which refers to Drummond's theory, and a family support scale (α = 0.949) which refers to Friedman's theory. The research data were analyzed using multiple regression tests. The results of the partial test showed that the higher the craving in people with an addiction who had undergone rehabilitation, the higher their tendency to relapse. However, the results of the partial test also proved that solid family support made the tendency to relapse lower. The results of the study simultaneously also showed that craving and family support were predictors of the tendency to relapse in drug addicts after rehabilitation. These findings are expected to broaden understanding of clinical psychology and provide practical guidelines for former addicts to prevent relapse through efforts to reduce cravings and increase family support.